Abscisic Acid Signaling and Abiotic Stress Tolerance in Plants: A Review on Current Knowledge and Future Prospects - Vishwakarma, Kanchan; Upadhyay, Neha; Kumar, Nitin; Yadav, Gaurav; Singh, Jaspreet; Mishra, Rohit K.; Kumar, Vivek; Verma, Rishi; Upadhyay, R. G.; Pandey, Mayank; Sharma, Shivesh (Frontiers in Plant Science, 2017)
Abiotic stress is one of the severe stresses of environment that lowers the growth and yield of any crop even on irrigated land throughout the world. A major phytohormone abscisic acid (ABA) plays an essential part in acting towards varied range of stresses like heavy metal stress, drought, thermal or heat stress, high level of salinity, low temperature and radiation stresses. It also finds its role in various developmental processes including seed germination, seed dormancy, and closure of stomata. Abscisic acid acts by modifying the expression level of gene and subsequent analysis of cis- and trans-acting regulatory elements of responsive promoters. It also interacts with the signaling molecules of processes involved in retorting to stresses and development of seeds. On the whole, the stress to a plant can be susceptible or tolerant by taking into account the coordinated activities of various stress-responsive genes. Numbers of transcription factor are involved in regulating the expression of abscisic acid responsive genes by acting together with their respective cis‑acting elements. Hence, for improvement in stress-tolerance capacity of plants, it is necessary to understand the mechanism behind it. On this ground, this article enlightens the importance and role of ABA signaling with regard to various stresses as well as regulation of abscisic acid biosynthetic pathway along with the transcription factors for stress tolerance.